The Safe Path at the Fork: Ensuring Replication-Associated DNA Double-Strand Breaks are Repaired by Homologous Recombination - Nickoloff, Jac A.; Sharma, Neelam; Taylor, Lynn; Allen, Sage J.; Hromas, Robert (Frontiers in Genetics, 2021)
Cells must replicate and segregate their DNA to daughter cells accurately to maintain genome stability and prevent cancer. DNA replication is usually fast and accurate, with intrinsic (proofreading) and extrinsic (mismatch repair) error-correction systems. However, replication forks slow or stop when they encounter DNA lesions, natural pause sites, and difficult-to-replicate sequences, or when cells are treated with DNA polymerase inhibitors or hydroxyurea, which depletes nucleotide pools. These challenges are termed replication stress, to which cells respond by activating DNA damage response signaling pathways that delay cell cycle progression, stimulate repair and replication fork restart, or induce apoptosis. Stressed forks are managed by rescue from adjacent forks, repriming, translesion synthesis, template switching, and fork reversal which produces a single-ended double-strand break (seDSB). Stressed forks also collapse to seDSBs when they encounter single-strand nicks or are cleaved by structure-specific nucleases. Reversed and cleaved forks can be restarted by homologous recombination (HR), but seDSBs pose risks of mis-rejoining by non-homologous end-joining (NHEJ) to other DSBs, causing genome rearrangements. HR requires resection of broken ends to create 3’ single-stranded DNA for RAD51 recombinase loading, and resected ends are refractory to repair by NHEJ. This Mini Review highlights mechanisms that help maintain genome stability by promoting resection of seDSBs and accurate fork restart by HR.